Unravelling early childhood pre-service teachers’ implicit stereotypes of scientists by using the repertory grid technique - Yilmaz-Na, Elanur; Sönmez, Elif (Springer Science and Business Media LLC, 2023)
AbstractConsidering teachers’ roles in developing children’s scientific literacy in preschools, a better understanding of pre-service teachers’ conceptualizations about scientific inquiry and scientists’ practices that have an impact on the science teaching practices offered to their future students is very much needed. Stereotypes were examined here as a component or root for many of the explanations for pre-service teachers’ conceptualizations about scientists. Aligned with the interpretivist paradigm, this phenomenographic study was, mostly qualitative in nature, specifically concerned with exploring pre-service teachers’ stereotypes of scientists by using the repertory grid technique, in which they perceived and differentiated between scientists. 119 early childhood pre-service teachers were recruited. Various types of analysis were carried out to analyze the data gathered in each repertory grid. We investigated the original 66 elicited bipolar constructs into 28 aggregated bi-polar construct groupings, systematically categorized into four bi-polar categories: (1) Recognition vs. Disregarded, (2) Scientific Integrity vs. Misconduct, (3) Communal vs. Dissociation, and (4) Agentic vs. Passivity. The findings suggest that pre-service teachers had typical stereotypical traits of scientists like being introverted, intelligent loners, into experiments and masters in their field with often-unrecognizable female figures. However, there was no association between gender, grade, and stereotypes of scientists elicited in the study. These types of stereotypes of scientists might potentially threaten effective science teaching at early ages. Science education practices can be rooted in these stereotypes of pre-service teachers. Considering these findings, structural changes in science education practices in teacher education programs are very much needed. This study also seems to confirm the importance of using the repertory grid technique as a good starting point to expose especially the implicit stereotypes of pre-service teachers about “who does science”, “how scientists think” and “what scientists do” before their actual actions in future classrooms.
Keywords: Early childhood education; Stereotypes of scientists; Science; Q; Pre-service teachers; Repertory grid technique; Phenomenographic study; Theory and practice of education; LB5-3640; 4. Education